Financial Inclusion and Carbon Emissions in ASEAN-6: Empirical Evidence from Panel Data - M. Aulia Rachman; Shanty Oktvilia; Dwi Rahmayani (Jurnal Ilmu Ekonomi Terapan, 2026)
Objective: This empirical research examines the impact of financial industry performance, through inclusive financial indicators, on carbon emissions in ASEAN-6 countries. It will examine the impact of financial inclusion on environmental damage with GDP per capita, Trade Openness, Inflation, and Interest Rate as control variables. Design/Methods/Approach: The financial inclusion index variable is calculated based on accessibility, availability, and usability. The analysis tool used is the Panel Regression with random effect models approach in ASEAN-6 countries from 2013 to 2019. The dependent variable is carbon emissions, and the independent variables are the financial inclusion index (including the three aspects of accessibility, availability, and usability), GDP per capita, trade openness, inflation, and interest rates. The research variable data is taken from the World Development Index (WDI) sourced from the World Bank. Findings: The estimation results show that financial inclusion, especially in the distribution of loans (usability), has a positive impact on environmental degradation. The higher the use of domestic credit, the higher the amount of carbon emissions. GDP and Trade Openness variables also have a similar effect; however, interest rates have a negative impact. Originality/Value: This research contributes to understanding the impact of financial inclusion on carbon emissions in ASEAN countries. Unlike previous research, this study attempts to analyze the three aspects of the financial inclusion index (accessibility, availability, and usability) that influence vulnerability to carbon emissions. This allows for a deeper understanding of these components to be justified in the context of more specific literature. Practical/Policy implication: Carbon emission mitigation efforts in ASEAN need to implement an integrated strategy through a regional integration framework that includes the Green Taxonomy, Sustainability-Based Credits, lower green loan interest rates, green tariff incentives, and the adoption of Climate Risk Reporting (TCFD) to direct capital allocation toward low-carbon development.